Central bank communications and the general public - Haldane, A; McMahon, M (American Economic Association, 2018)
Despite the recent revolution in central bank communication, it is unclear the general public have benefitted from these enhanced central bank communications. We first analyze the growth of communication and some reasons that the public may have missed the revolution. We then discuss the desirability of greater communication with the public. The case for feasibility of such communication examines observational and experimental evidence following the recently adopted use of a layered communication at the Bank of England. We find that, while more research is needed, there are compelling reasons for central banks to continue trying to target communication at the public.